Characterization of Musculoskeletal Injury Risk in Dungeness Crab Fishing. Issue 2 (3rd April 2023) - Kim, Jeong Ho; Vaughan, Amelia; Kincl, Laurel
ABSTRACT: Objectives: Commercial Dungeness crab fishermen's manual crab pot handling activities can be done in harsh outdoor working environments at sea and can pose well-known physical risk factors associated with musculoskeletal injury including forceful exertion, repetition and awkward posture. The nonfatal injury rate in this fishing fleet is 3.4 per 1, 000 full-time equivalent workers. Two-thirds of self-reported injuries in the fleet were musculoskeletal sprains and strains. To date, no objective biomechanical assessment of musculoskeletal disorder (MSD) risk has been conducted due to the challenging work environment. Methods: The aim of this study was to determine the feasibility of collecting objective biomechanical assessments (i.e., posture and repetition) using inertial measurement unit (IMU) sensors placed on the arms and torso of professional deckhands (n = 7) while at sea, harvesting Dungeness crab. Based on the IMU-measured posture data, fishermen's anthropometry, and crab pot weights, biomechanical loading of the low back and both shoulders was estimated. Results: The IMU sensor data showed that commercial Dungeness crab fishing is highly repetitive and poses awkward postures in the shoulders and back. The estimated static low back compression, shear force, and flexion moment about the shoulders and low back (L5/S1) indicate potential injury risk associated with harvesting crab. Conclusion: The results indicate that objective biomechanical assessment using the IMU sensors is feasible in the commercial fishing environment.